The role of internal audit functions with regard to audit outcomes at South African municipalities - Mamaile, L. J. (International Conference on Public Administration and Development Alternative (IPADA), 2019)
The internal audit functions are expected to assist their organisations, including the municipalities to identify and resolve the challenges faced by these organisations. The internal audit functions (IAFs) are expected to play a number of roles to add value to their municipalities, including oversight role, detection role, insight role and deterrence role. Although IAFs are instruments with the expertise to assess efficient utilisation of financial resources within the municipalities and help improve oversight and financial performance, research has paid little attention to the role of IAFs in the financial management process. As a result, South African municipalities have been obtaining negative audit outcomes from the Auditor general South Africa (AGSA) over the years. This paper relied on AGSA reports in South Africa in establishing what role the IAFs are playing in municipalities, and whether they have any role to play in assisting the municipalities in obtaining the desired audit outcomes. Therefore, the data was collected from the AGSA audit reports for the period of five years, being the period from 2013/2014 to 2017/2018 financial years. The paper suggests that there is limited contribution or no contribution made by the IAFs in South African municipalities towards the achievement of positive audit outcomes by the municipalities. Keywords: Internal audit functions, Local government, Municipalities, Value-adding
The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Internal audit functions; Local government; Municipalities; Value-adding; Audit committees - Law and legislation; Management audit; Municipal government